(untitled) - Halliday, David (New York, 2002)
The 5th edition of "Physics" has been edited to clarify conceptual development in light of recent findings from physics education research, and the mechanics sequence has been re-organized to that energy is a capstone topic. The presentation of thermodynamics and quantum mechanics has been updated to provide a more modern approach, and the end-of-chapter problem sets have been thoroughly over-hauled: new problems added; out-dated reference deleted; and new short-answer conceptual questions added. The supplements package has been expanded to include more materials for student and instructor.
Keywords: Vật lý,Physics,Physics